Green Consumer Behavior Profile Of Elementary School Students In The City Of Bandung - Deasy Rahmawati; Nana Supriatna; Sapriya (International Conference on Elementary Education, 2023)
. The purpose of this study was to obtain an overview of the green consumer behavior profile of elementary school students in the city of Bandung, to what extent they apply the concepts of green consumer behavior and how potential elementary school students implement green consumers in their daily lives. Students with good green consumption behavior whose actions are always in harmony with nature and are responsible for the surrounding environment, consider the effect of their consumption activities on the environment which is reflected in how these students search for, buy, use, evaluate, and dispose of products. This study uses a quantitative approach with the survey method, with the instrument in the form of a Green Consumer Behavior questionnaire. The population used in this study were public elementary school students in the city of Bandung, the samples were taken using probability sampling technique. Sampling of members of the population is done randomly and members of the population are considered homogeneous (simple random sampling). The research procedure consists of three stages, namely: (1). preparation phase. At this stage it is carried out by compiling research instruments, compiling research instruments; (2). Data Collection Stage. This stage begins by distributing questionnaires to respondents in the form of a Google form. Respondents filled out/answered a questionnaire in the form of a Google form via their mobile phone or laptop/PC, then the respondent's data was sent automatically via the researcher's Gmail account for further processing and analysis; and (3). Completion Stage. The completion stage is the final stage of the research, namely researchers processing and analyzing research data to draw conclusions. The results of the research from 400 student respondents with 6 questions distributed showed that 1 question was included in the very good category, 2 questions were included in the good category and 3 questions were included in the sufficient category. These questions are an illustration of the profile of green consumer behavior in students. The profile of green consumer behavior of elementary school students in the city of Bandung shows that the behavior of choosing/buying food/goods that do not harm the body is very well done, while the behavior of bringing cutlery and drinking from home and sorting wet/dry waste is well done by school students Base.